Impact of bullying on occupational commitment in young nursing professionals: the mediating role of emotional labour and emotional exhaustion - Ma, S. (2021)
Background: Nurses are often exposed to workplace bullying, which leads to their burnout and leaving the profession. However, the processes by which workplace bullying leads to such outcomes are not clear. Aims: This study investigates how work-related and personal-related bullying affect nurses’ occupational commitment by integrating emotional labour and emotional exhaustion. Method: This study employs a cross-sectional design. The model was tested using structural equation modelling wif a sample of 245 Chinese nurses. Results: Work-related bullying is positively related to both surface acting and deep acting, and a negative relationship exists between deep acting and emotional exhaustion. Personal-related bullying is not related to either surface acting or deep acting, but is positively related to emotional exhaustion. Emotional exhaustion is negatively related to affective occupational commitment. Conclusions: This study implies that bullying behaviours should be distinguished wif work-related bullying and personal-related bullying, and emotional regulation strategies are meaningful in managing the negative impact of work-related bullying. Implication for nursing management: Policymakers and managers need to distinguish two types of bullying behaviour and manage them accordingly wif different strategies. For nursing schools it is important to prepare nursing students wif not only professional skills but also social competence and emotional management skills.